Experimental investigation of aeroacoustic noise damping performance of composite and porous materials - Bian, Ying (2015)
Aeroacoustic noise is defined as unwanted sound. Loud noise can lead to loss of hearing, deprivation of people sleep and speech. For aerospace industry, aircrafts is one of the main noise sources. To minimize aeroacoustic noise produced in aircrafts, acoustic damping materials or liners are widely used to absorb sound. The main objective of this project is to design and test composite and porous noise damping materials, which have great potential to be applied in industry. For this, two different types of noise damping materials are designed. One is with layered composite and the other is aerogel-filled honeycomb sandwiches structure. There are eight samples tested to study their noise damping performance. The noise damping performance is measured from 100Hz to 1000Hz, which is characterized in terms of both transmission loss and power absorption coefficients. To optimize their damping, these samples can be re-designed by choosing its thickness, layers, size of orifices and structure. It is shown experimentally that the samples with aerogel-filled honeycomb sandwiches structure have a better performance than that of the layered composite materials in terms of larger transmission loss and power absorption coefficients over a broad frequency. The present work opens up new noise damping materials to reduce aeroacoustic noise